Management Education and Earth System Science: Transformation as if Planetary Boundaries Mattered. Issue 1 (January 2021) - Edwards, Mark G.; Alcaraz, Jose M.; Cornell, Sarah E.
Earth system science (ESS) has identified worrying trends in the human impact on fundamental planetary systems. In this conceptual article, we discuss the implications of this research for business schools and management education (ME). We argue that ESS findings raise significant concerns about the relationship between business and nature and, consequently, a radical reframing is required to embed economic and social activity within the global sustainability of natural systems. This has transformative implications for ME. To illustrate this reframing, we apply the ESS lenses of social-ecological interdependence, multiscalar relations, environmental governance, and environmental values to the ME functional domains of institutional purpose, social context and engagement, pedagogical practice, curricular design, and research focus. Our work contributes to the literature on business education for sustainability and the business-society-nature nexus. We explore and apply key ESS findings and concepts, discuss normative implications of these ideas, and offer guidance on transformational pathways for business schools and ME.